Answer:
960 ways
Step-by-step explanation:
Multiplication Principle: if there are n ways to do one thing and m ways to do another, then there are m x n ways to do both.
That can expand to include three things (or more).
8 x 10 x 12 = 960
Answer:
Step-by-step explanation:
Convert mixed fraction to improper fraction.
÷
=
÷ ![\frac{1}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D)
Now use K C F method
K - Keep the first fraction
C - Change the division operation to multiplication
F- Flip the second number
![= \frac{9}{4} *\frac{2}{1}\\\\= \frac{9}{2}*1\\\\= \frac{9}{2}\\\\= 4 \frac{1}{2}](https://tex.z-dn.net/?f=%3D%20%5Cfrac%7B9%7D%7B4%7D%20%2A%5Cfrac%7B2%7D%7B1%7D%5C%5C%5C%5C%3D%20%5Cfrac%7B9%7D%7B2%7D%2A1%5C%5C%5C%5C%3D%20%5Cfrac%7B9%7D%7B2%7D%5C%5C%5C%5C%3D%204%20%5Cfrac%7B1%7D%7B2%7D)
I believe it would be 6 due to the radius being a half of the actual circumfrence
Answer:
x = 1, y = 2, z = -1
Step-by-step explanation:
2x + 4y = 10
2x = -4y + 10
x = -2y + 5
now sub -2y + 5 in for x, back into the other 2 equations
2x + 2y + 3z = 3 -3x + y + 2z = -3
2(-2y + 5) + 2y + 3z = 3 -3(-2y + 5) + y + 2z = -3
-4y + 10 + 2y + 3z = 3 6y - 15 + y + 2z = -3
-2y + 3z = 3 - 10 7y + 2z = - 3 + 15
-2y + 3z = - 7 7y + 2z = 12
-2y + 3z = -7....multiply by 2
7y + 2z = 12...multiply by -3
--------------------------
-4y + 6z = -14 (result of multiplying by 2)
-21y - 6z = -36 (result of multiplying by -3)
---------------------------add
-25y = - 50
y = -50/-25
y = 2 <===
2x + 4y = 10 2x + 2y + 3z = 3
2x + 4(2) = 10 2(1) + 2(2) + 3z = 3
2x + 8 = 10 2 + 4 + 3z = 3
2x = 10 - 8 6 + 3z = 3
2x = 2 3z = 3 - 6
x = 2/2 3z = -3
x = 1 <== z = -3/3
z = -1 <===